Clinical and histopathological assessment of the combined therapeutic effect of Curcumin Nanoparticles and PRP on the cutaneous wound repair in rats. - Ghallab, Mohamed R.; Abdel-Hady, Abdel Nasser A.A.; Youssef, Mohamed; Salah, Mohammed; Mawas, Amany S. (Journal of Advanced Veterinary Research, 2024)
Skin wound healing is a complex biological process in which the replacement of dead tissue by a vital one takes place. The aim of this study is to assess the clinical and histopathological modalities of Curcumin nanoparticles and (Platelet-rich plasma) application on excisional skin wound healing activity. Under complete aseptic conditions full-thickness (10 mm) artificial uniform skin wounds were created on the back of twenty anaesthetized male rats (divided into four groups; Control (Group A), Curcumin treatment (Group B), Platelet-rich plasma treatment (Group C), and Curcumin - Platelet-rich plasma treatment (Group D). Tissue sections were stained by hematoxylin and eosin, PAS, and Crossman trichrome for histopathological evaluation of the wound healing properties following the curcumin and PRP topical treatment. Significant skin regeneration including wound closure and histopathological healing was better in Curcumin nanoparticles and PRP treated groups compared to the control untreated one through better reepithelization and coaptation between the epidermis and dermal layers, more vascular angiogenesis, less inflammatory reactions, healthy granulation tissue and better collagen fibers density in the dermal layer. The obtained results proved an effective external therapeutic use of both Curcumin and PRP on cutaneous wound healing progression.